Making online teaching accessible : inclusive course design for students with disabilities - Coombs, Norman, 1932- (San Francisco : Jossey-Bass, 2010)
"As educational institutions rapidly expand into online and hybrid formats, designing with accessibility in mind becomes essential. This book helps online teachers, instructional designers, and content developers avoid inadvertently creating barriers for students with disabilities and comply with government-mandated ADA standards. Grounded in the theories of learner-centered teaching and successful course design, the book explains how to design course content and delivery to be both attractive and accessible to all students, creating better conditions for student learning, success, and satisfaction, and better preparing students to compete in the competitive workplace."--
1. Creating a level learning space : How people with disabilities use computers ; Universal design and online learning ; Legislation, decisions, and guidelines governing online learning ; Decisions of the Department of Education's Office for Civil Rights ; Review of OCR decisions and online learning -- Take-aways from this chapter -- 2. Online learning and students with disabilities : Accessibility of the online learning infrastructure ; Creating accessible online course content ; The students' part of the equation ; Take-aways from this chapter -- 3. Creating accessible content in Word and Excel : An introduction to structuring documents in Word ; Creating well-structured documents ; Selecting style attributes to enhance accessibility ; Creating a table of contents ; Making images in Word accessible ; Creating Word tables and Excel spreadsheets ; Take-aways from this chapter -- 4. Creating accessible presentations with PowerPoint : PowerPoint and universal design ; Designing accessible PowerPoint presentations ; Creating narrated slide shows ; Take-aways from this chapter -- 5. Delivering accessible content : A word about file types ; Distributing accessible word documents ; PDF documents ; Distributing Excel spreadsheets ; Distributing accessible PowerPoint content ; Online accessibility checkers ; Take-aways from this chapter -- Science, technology, engineering, and math : Historical issues with math accessibility ; Authoring accessible electronic math documents ; Issues with technical graphics ; Providing accessible graphics ; Take-aways from this chapter -- 7. Making multimedia accessible : The role of multimedia in online learning ; Creating a transcript ; Adding synchronized captions to a video ; Accessibility for real-time audio or video ; Take-aways from this chapter -- 8. Supporting accessible online learning : The need for institution-wide support ; The role of student disability services ; Awareness and skills training ; Administration support for online learning ; Take-aways from this book -- Appendices : A. Section 508 web standards ; B. WebAIM summary of W3C WAI WCAG2 ; C. American Foundation for the Blind's distance learning survey.
Includes bibliographical references and index.
Keywords: Students with disabilities -- Computer-assisted instruction; Computers and people with disabilities; Inclusive education